Multimorbidity and tooth loss: data from Chilean National Health Survey 2016-2017 - Matías Santos-López; Priscila Gómez-San Martín; Paula Margozzini; Duniel Ortuño (BMC, 2024)
Abstract Background Oral diseases are a significant global public health challenge. Current evidence indicates that several chronic conditions are individually associated with tooth loss. People are living with more than one chronic condition, known as multimorbidity (MM). Considering the common risk factors for oral and chronic diseases, this study aimed to evaluate the association between MM and tooth loss in the Chilean population. Methods Cross-sectional study with secondary data from the latest Chilean National Health Survey (ENS 2016-17). The number of remaining teeth was classified into four groups: functional dentition (≥ 20 remaining teeth), moderate tooth loss (10 to 19), severe tooth loss (1 to 9), and edentulism (0). MM was defined based on the number of chronic conditions as a binary variable (MM≥ 2) and as a 4-level categorical variable (MMG0−G3), G0: none, G1: 1, G2: 2-4, and G3: ≥5 conditions. Stratified analysis by age group (< 65, ≥ 65 years) was performed. Mean and SD were calculated for crude and adjusted remaining teeth. Significance level was set to 0.05. Prevalence ratios were estimated with Poisson regression models with robust variance, crude and adjusted for sex, age, geographic area, and educational level. Logistic regressions models were fitted to calculate odds ratios as a sensitivity analysis. Results Of 4,151 adults aged 17-98, 54.9% had MM and the prevalence of moderate, severe tooth loss and edentulism was 25.4%, 6.9% and 4.8% respectively. Adults aged ≥ 65 years with MM≥ 2 were 1.66 [1.04-2.66] times more likely to have severe tooth loss than those without MM. Adults aged < 65 years with MMG3 were 1.76 [1.12-2.77] times more likely to have moderate tooth loss and 2.55 [1.02-6.36] times more likely to have severe tooth loss than those without MM. Conclusions In this study, we found statistically significant associations between the number of chronic conditions and moderate/severe tooth loss in both analyzed age groups. These findings highlight the need to provide oral health care for adults with multimorbidity using a person-centred model and to seek strategies to prioritize health care.